2018
DOI: 10.1177/1042258718774916
|View full text |Cite
|
Sign up to set email alerts
|

National Business Regulations and City Entrepreneurship in Europe: A Multilevel Nested Analysis

Abstract: This article provides and tests a theoretical framework with a multilevel (country–city) nested model to analyze the relationship between national business regulations (NBRs) and city level entrepreneurship. While public interest theory predicts a positive relationship between NBR and city level entrepreneurship, public choice theory predicts the opposite, a negative relationship. Based on multilevel analysis for a matched country–city panel of 228 cities across 20 European countries for the years 2004 to 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 67 publications
(154 reference statements)
5
90
1
Order By: Relevance
“…3 Entrepreneurship and knowledge: bridging a micro-industry-macro divide Entrepreneurship policy is by nature multi-level and multi-dimensional (Audretsch et al 2018). It can be understood at the individual level of analysis (Casson 2005;Autio et al 2014), regional level (Audretsch and Lehmann 2005;Audretsch et al 2015a, b), industry level (Qian 2018; Colombelli and Quatraro 2018), national level (Acs et al 2014(Acs et al , 2017Audretsch and Lehmann 2016), and international level, resulting in a complex multi-level structure of entrepreneurship activities (Estrin et al 2013;Belitski and Desai 2016b).…”
Section: Internal and External Knowledge In Entrepreneurship Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Entrepreneurship and knowledge: bridging a micro-industry-macro divide Entrepreneurship policy is by nature multi-level and multi-dimensional (Audretsch et al 2018). It can be understood at the individual level of analysis (Casson 2005;Autio et al 2014), regional level (Audretsch and Lehmann 2005;Audretsch et al 2015a, b), industry level (Qian 2018; Colombelli and Quatraro 2018), national level (Acs et al 2014(Acs et al , 2017Audretsch and Lehmann 2016), and international level, resulting in a complex multi-level structure of entrepreneurship activities (Estrin et al 2013;Belitski and Desai 2016b).…”
Section: Internal and External Knowledge In Entrepreneurship Researchmentioning
confidence: 99%
“…This paradox of the firm knowledge production function was described by Audretsch (1995) and later by and Acs et al (2013) as the Knowledge Spillover Theory of Entrepreneurship (KSTE). The major thrust of this and subsequent work is that firms endogenously seek knowledge in a regional Lehmann 2005, 2006), industrial (Qian and Acs 2013), and ecosystem context (Audretsch et al 2018;Stam 2018), aiming to create and recombine existing knowledge available in the economy into knowledge inputs, which can lead to the generation of new products and services (Ghio et al 2015). Acs et al (2013) and Ghio et al (2015) empirically demonstrated how the knowledge production function works for entrepreneurs.…”
Section: Internal and External Knowledge In Entrepreneurship Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixed embeddedness concept that acknowledges that ethnic entrepreneurs are embedded in both social contexts and opportunity structures, could be one way to operationalise such a multi-layered approach (Kloosterman & Rath 2001). While in quantitative research multilevel approaches of entrepreneurship are on the rise (Audretsch et al 2018), for qualitative research this would mean data collection of contexts and persons in multiple social arenas in which the entrepreneur is embedded (Rath 2002).…”
Section: New Research Pathsmentioning
confidence: 99%